USING COLLABORATIVE WRITING TO IMPROVE STUDENTS’ ENGAGEMENT IN WRITING A RECOUNT TEXT - Haran, Rosalia Teodora; Sofian, Sofian; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main objective of this research was to improve the students? engagement in writing a recount text using collaborative writing to the eighth grade students of SMP Negeri 4 Pontianak in academic year 2017/2018. The research was conducted with Classroom Action Research in three cycles and every cycle consisted of one meeting. The subject of this research was 31 students in class VIII B. The researcher used field notes and writing tests as tools of data collection. The result showed that the use of collaborative writing improved students? engagement in writing a recount text. The improvement of students? engagement could be seen from the students? performance in teaching and learning process. The studentsbecame more enthusiastic in offering ideas. The students showed their commitment, attention, and persistence in learning. The improvement of students? engagement was presented into 11% improvement of excellent category engagement and 38% improvement of good category engagement in the first cycle and 38% improvement of excellent category engagement in the second cycle. Keywords:  Collaborative Writing, Students? Engagement, Recount Texts Writing